2022
DOI: 10.3390/ph15030377
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Respiratory RNA Viruses by a Composition of Ionophoric Polyphenols with Metal Ions

Abstract: Controlling the infectivity of respiratory RNA viruses is critical, especially during the current SARS-CoV-2 pandemic. There is an unmet need for therapeutic agents that can reduce viral replication, preferably independent of the accumulation of viral mutations. Zinc ions have an apparent activity as modulators of intracellular viral RNA replication and thus, appear attractive in reducing viral RNA load and infectivity. However, the intracellular concentration of zinc is usually too low for achieving an optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Other studies have found similar results when comparing transformed cellular models to multiple primary cells ( 101 103 ). The transformed cell lines used in this study are widely employed, including studies that focus on transcription ( 104 ), inflammation ( 105 ), and virology ( 106 108 ), including HIV-1 ( 109 ). Our data demonstrate that these cells, however, do not accurately model the transcriptome of primary cells, and thus their utility may be limited in some settings.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found similar results when comparing transformed cellular models to multiple primary cells ( 101 103 ). The transformed cell lines used in this study are widely employed, including studies that focus on transcription ( 104 ), inflammation ( 105 ), and virology ( 106 108 ), including HIV-1 ( 109 ). Our data demonstrate that these cells, however, do not accurately model the transcriptome of primary cells, and thus their utility may be limited in some settings.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen radicals such as superoxide, hydroxyl radicals, and lipid peroxyl radicals are known to increase during virus infection [55], and flavonoids can capture and eliminate them. Other studies have reported flavonoids as agents that protect the lungs from the adverse effects of oxygen-derived free radicals released during influenza virus infection [56], carriers of metal ions as ionophores [57], and 5-lipoxygenase [32,33], which are involved in lipid oxidation reactions. The Keap1-Nrf2 system plays an important function in the control mechanism of this biological response.…”
Section: Potential Of Prenylated Flavonoids In Antiviral Strategiesmentioning
confidence: 99%
“…ZnO nanoparticles have been reported to activate the cellular antioxidant defense system and thus improve the remission of dextran sulfate sodium (DSS)-induced colitis in mice . Although the combination of flavonoids and zinc ions can improve the ability to fight viruses, including COVID-19, no studies have been reported on their combination treatment in IBD. , …”
Section: Introductionmentioning
confidence: 99%